2013
DOI: 10.1007/s00234-013-1136-y
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of ruptured blister-like aneurysms with special reference to the flow-diverting strategy

Abstract: Endovascular reconstructive treatment of a ruptured BA using a flow-diverting device is a promising strategy that can be performed with acceptable clinical and good radiological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…On long-term follow-up angiography the aneurysm was completely obliterated in seven patients. In another case series by Çinar et al 23 the authors reported a series of seven BAs all located in the supraclinoid ICA. In their series, flow diversion with PED was carried out in all but one patient who was treated by parent artery occlusion.…”
Section: Discussionmentioning
confidence: 98%
“…On long-term follow-up angiography the aneurysm was completely obliterated in seven patients. In another case series by Çinar et al 23 the authors reported a series of seven BAs all located in the supraclinoid ICA. In their series, flow diversion with PED was carried out in all but one patient who was treated by parent artery occlusion.…”
Section: Discussionmentioning
confidence: 98%
“…3 Çinar et al published a 7-patient ruptured blister aneurysm series with PED treatment and reported good clinical outcome in 71% and no procedural or postprocedural aneurysm rerupture. 4 A series of 11 ruptured blister aneurysm cases treated with the Silk flow diverter reported good clinical outcomes in 92%, no aneurysmal reruptures, and a procedural minor ischemic stroke in 1 case. 1 A challenging aspect of flow-diversion treatment of ruptured blister aneurysms is the necessity of concomitant dual antiplatelet therapy to minimize the risk of device thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Single device placement occurred in the majority of reported case series; 1,3,4,17,29,31 although aneurysmal rerupture in a patient who had recently undergone flow diversion while receiving dual antiplatelet agents has been reported. 19 Therefore, current practice strategies for ruptured blister aneurysms also include placement of multiple telescoped overlapping flow diverters to minimize the risk of postdiversion rerupture and to speed parent vessel endothelialization and exclusion of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for the treatment of these lesions has not been established. The outcome from the different endovascular strategies varies in the literature 2 5 9 10. Intraoperative rupture and delayed recurrence remain significant problems using stent-assisted coil embolization 2 5 11–13.…”
Section: Discussionmentioning
confidence: 99%